The Dialectical Relationship between Religious Moderation and Islam Nusantara in Indonesia - Nurhanisah, Nurhanisah; Tjoetra, Afrizal (Program Studi Aqidah dan Filsafat Islam, 2025)
The concepts of religious moderation and Islam Nusantara serve as fundamental pillars in the discourse of Indonesian Islam, both promoting values of tolerance, peace, and openness. Although frequently associated, their interplay has rarely been examined through a dialectical lens that highlights both their tensions and convergences. This study fills this gap by critically analyzing the discursive intersections and ideological frictions between these two concepts. Using a qualitative descriptive method based on extensive literature review, the article explores normative perspectives alongside critical debates within public and academic spheres. Findings reveal significant common ground in the contextualized Islamic praxis embodied by Islam Nusantara, yet misunderstandings persist due to low ideological literacy and politicization of religious narratives. The study positions Islam Nusantara as a localized manifestation of religious moderation capable of bridging religious and national identities. It contributes theoretically by broadening understanding of moderate Islam rooted in local culture and offers practical implications for strengthening inclusive, context-aware Islamic narratives that can counter ideological polarization and foster social cohesion in Indonesia.